Promoting Digital Literacy for the Prevention of Risk Behavior in Social Media for Adolescents - Sugeng, Sugeng; Fitria, Annisa; Adi Nur Rohman , Adi Nur Rohman (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
This article examines the internet and social media which are increasingly used by the public, especially among teenagers. Through digital technology, people are constantly connected to each other. Along with the rise of various risky behaviors and crimes that use information technology, both as a means and a target. Based on doctrinal studies, the results show that regulations related to information technology and the Internet have not yet reached digital platform providers in creating a secure digital space. Sanctions and penalties for law violations and crimes are only intended for social media users. Efforts to create a safe and civilized digital space are carried out through policy breakthroughs, both at the ministry level and law enforcement agencies. The vulnerability of adolescents to threats in the digital space needs to be overcome with the support of the family as the smallest unit of society, through strengthening digital literacy. Digital skills are expected to improve youth’s ability to use the internet and social media for productive and useful activities. Digital literacy policies for teenagers are not only the responsibility of the state, but also the community, educators, and families.